In Vitro Study of MefenamateStarch as Drug Delivery System (Baghdad Science Journal, 2025)
Mefenamic acid was esterified with starchwith[1:1] Molar ratio, as drug substituted with natural polymer, to prolongthe period of hydrolysis of drug polymer with other advantages. The new prodrug starch was characterized by FT-IR and UV-Visible and 1H-NMR spectroscopies. The physical properties were studied and controlled drug release was studied in different pH values at 37oC. The stability of drug was carried out by measuring the absorbance of mefenamic starch which hydrolyzed in HCl solution of pH 1.1 (artificial gastric fluid) and phosphate buffer of pH 7.4 (simulating intestinal fluid SIF) at 37oC for several days. The thermal analysis such as DSC was studied.